PROMOTING SUSTAINABLE TRAVEL BEHAVIOR THROUGH TRANSPORT POLICY MEASURES - Nasrudin, Na'asah; Abdullah, Yusfida Ayu; Hoon Leh, Oliver Ling (PLANNING MALAYSIA, 2017)
This paper examines how transport policy measures have influenced travel behaviour to promote sustainable transportation. Data were collected through a survey on 384 vehicle users to represent the 36 sections of Shah Alam, Selangor. This paper also studied the readiness of an urban population to reduce car usage. Maj ority of the respondents stated that the increase in petrol and toll prices would be the key factors to reduce car use, and more provision of public transport would encourage them to use public transport. However, Chi-square test showed that the willingness of the respondents to use public transport has a strong relationship with the frequency of driving a vehicle. The level of willingness to use public transport is lower when a car is used more frequently. Results also suggested that the majority of the respondents were not ready to consider cycling and walking as alternatives.